APLIKASI PERLAKUAN PENDAHULUAN PULSED ELECTRIC FIELD (PEF) PADA EKSTRAKSI TANIN BIJI PINANG (Areca catechu) (KAJIAN FREKUENSI DAN WAKTU PEF) - Nur Lailatul Rahmah, Sukardi, dan Irwina Nova Dila (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Areca catechu contains tannins compounds acting as antioxidants. Extraction process is required to obtain these compounds from areca nut. Pretreatment before extraction using Pulsed Electric Field (PEF) has shown improvement of yield as well as the quality of antioxidant extracts compared with control. The experimental design of this research was Factorial Random Design with two factors. The first factor was frequency of PEF with three levels of 1, 1.5, and 2 kHz and the second factor was PEF application time with three levels of 20, 25, and 30 seconds. The extract of areca seed from PEF extraction with combination of frequency and time of PEF using magnetic field 450 v/cm did not provide significanty different yield and quality. The selection of best treatment was based on the economic aspects and analysis of variance, since there was no significant difference between each parameter and treatment. The best frequency and duration of PEF on yield and antioxidant quality of areca nut extract were 1 kHz and 20 second with a yield of 5.6%; moisture content of 7.78%; IC50 value of 277,56 ppm; and tannins content of 442.36 mg GAE/g. FTIR spectrophotometric analysis results showed that the resulting absorption has a functional group that supports the presence of tannins.Keywords: fresh areca nut, electroporation, electrical pulse